TAHAP PENGGUNAAN PEMBELAJARAN MAYA DALAM KALANGAN GURU REKE BENTUK TEKNOLOGI: SATU TINJAUAN DI SEKOLAH RENDAH LUAR BANDAR - Sern, Lai Chee; Kamarudin, Noormawati; Lip, Rashidah; Hasnan, Noridah (Online Journal for TVET Practitioners, 2017)
In line with the seventh shift, namely transforming national educational system, as stated in the Malaysia Education Blueprint (2013-2025), the Malaysian government has prepared internet access and virtual learning environment through 1BestariNet in 10,000 school across Malaysia which is inclusive of rural primary schools. Virtual learning environment (VLE), which is learning platform, has become the major agenda in primary schools. Specifically, VLE Frog has been untiled by primary school teachers as a teaching platform. Therefore, this survey was conducted to find out the level of usage of VLE Frog for teaching and learning among teachers who teach the subject of Design and Technology at rural primary schools in Batu Pahat District. In addition, this research also aimed at investigating the main problems faced by the primary school teachers in using VLE Frog. A total of 36 teachers from 18 rural schools were invited to participate in this research. Questionnaire was used for data collection. The findings revealed that the level of usage of VLE Frog was medium. Apart from that, the current outcomes also indicated that internet connection was perceived as the main problem faced by the teachers who used VLE Frog to teach Design and Technology at rural primary schools in district of Batu Pahat.